Review: Tissue Engineering of Small-Diameter Vascular Grafts and Their In Vivo Evaluation in Large Animals and Humans - Shu Fang; Ditte Gry Ellman; Ditte Caroline Andersen (Cells, 2021)
To date, a wide range of materials, from synthetic to natural or a mixture of these, has been explored, modified, and examined as small-diameter tissue-engineered vascular grafts (SD-TEVGs) for tissue regeneration either in vitro or in vivo. However, very limited success has been achieved due to mechanical failure, thrombogenicity or intimal hyperplasia, and improvements of the SD-TEVG design are thus required. Here, in vivo studies investigating novel and relative long (10 times of the inner diameter) SD-TEVGs in large animal models and humans are identified and discussed, with emphasis on graft outcome based on model- and graft-related conditions. Only a few types of synthetic polymer-based SD-TEVGs have been evaluated in large-animal models and reflect limited success. However, some polymers, such as polycaprolactone (PCL), show favorable biocompatibility and potential to be further modified and improved in the form of hybrid grafts. Natural polymer- and cell-secreted extracellular matrix (ECM)-based SD-TEVGs tested in large animals still fail due to a weak strength or thrombogenicity. Similarly, native ECM-based SD-TEVGs and in-vitro-developed hybrid SD-TEVGs that contain xenogeneic molecules or matrix seem related to a harmful graft outcome. In contrast, allogeneic native ECM-based SD-TEVGs, in-vitro-developed hybrid SD-TEVGs with allogeneic banked human cells or isolated autologous stem cells, and in-body tissue architecture (IBTA)-based SD-TEVGs seem to be promising for the future, since they are suitable in dimension, mechanical strength, biocompatibility, and availability.